2017
DOI: 10.1155/2017/9724217
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Pretreatment Attenuates Hepatic Ischemia Reperfusion-Induced Apoptosis and Autophagy by Inhibiting ERK/NF-κB Pathway

Abstract: Background Hepatic ischemia reperfusion (IR) injury is a common phenomenon in transplantation or trauma. The aim of the present study was to determine the protective effect of quercetin (QE) on hepatic IR injury via the ERK/NF-κB pathway. Methods Mice were randomized into the sham, IR, QE100 + IR, and QE200 + IR groups. Quercetin was administered intragastrically daily at two doses (100 mg/kg and 200 mg/kg) for 5 days prior to IR injury. The expression levels of liver enzymes, inflammatory cytokines, and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 58 publications
(48 reference statements)
3
22
0
Order By: Relevance
“…Our study exhibited that the HI for 45 minutes followed by 3 hours of reperfusion led to the liver injury which is assessed by marked elevation of liver enzymes ALT and AST levels indicating damage in the cell membrane of the liver and this is in accordance with previous studies [ 25 , 35 , 36 ]. Moreover, hepatic necrosis, sinusoidal congestion, hemorrhage, and hepatocyte degeneration are the characteristic pathological changes seen after HIR [ 24 , 34 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study exhibited that the HI for 45 minutes followed by 3 hours of reperfusion led to the liver injury which is assessed by marked elevation of liver enzymes ALT and AST levels indicating damage in the cell membrane of the liver and this is in accordance with previous studies [ 25 , 35 , 36 ]. Moreover, hepatic necrosis, sinusoidal congestion, hemorrhage, and hepatocyte degeneration are the characteristic pathological changes seen after HIR [ 24 , 34 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…The protective effects of many Chinese herbal medicines, such as quercetin, [51][52][53] oleanolic acid, 54 proanthocyanidin B2, 55 epigallocatechin-3-gallate, 56 isorhamnetin 57 and genistein, 58 in liver diseases have been confirmed by our studies.…”
Section: Ppa Rγ Agonis Ts From Natur Al Produc Tssupporting
confidence: 79%
“…In addition, we also observed that sevoflurane significantly reduced the apoptosis of liver tissue cells. Apoptosis is a common phenomenon in the process of hepatic ischemia–reperfusion [ 25 , 26 ]. It has been reported that 50–70% of endothelial cells and 40–60% of hepatocytes underwent apoptosis during hepatic ischemia–reperfusion [ 27 ].…”
Section: Discussionmentioning
confidence: 99%